Nurse competence in implementing public health care - Suprapto Suprapto; Trimaya Cahya Mulat; Nur Syamsi Norma Lalla (Intelektual Pustaka Media Utama, 2021)
Health development is a way of increasing awareness, willingness and ability to live healthy for everyone so that an optimal degree of public health can be achieved. The purpose of knowing how the relationship between nurse competence and community health care activities. This study employed quantitative approach and correlation analysis. The population was nurses who work at public health center in Makassar City, Indonesia, however there were 118 nurses who meet the criteria in their selection. There were relationships between attitudes, skills, and competencies with the level of implementation of community health services and that there is an interaction between competence and training. The results of the competency analysis obtained an OR value of 6.429, meaning that public health center nurses who have good competence have a chance of 6.429 times to carry out community health care activities optimally. Most dominant with the implementation of public health care is the interaction between competence and training. The competence of nurses need to be improved in order to optimize the implementation of community health services through training, coaching through assigned teams, and collaborating with peers and providing support in the form of policies for rewards and sanctions such as nurse career paths.